TRANSLATION STRATEGIES OF BUSINESS-RELATED WORDS AND TERMS IN THE PRESS RELEASES OF EUROPEAN COMMISSION - Rosita Šimonytė Juškauskė; Ieva Brazauskaitė Zubavičienė; Jolanta Bareikienė; Asta Pukienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The paper aims to identify translation patterns of business-related words and terms applied while translating public information documents of the European Commission. The problem question is how business-related words and terms are conveyed from English (as the source language) into Lithuanian (as the target language) and what are the most common translation strategies used to achieve an efficient and accurate translation. The paper suggests the theoretical background of translation strategies and the practical analysis of 96 examples of business-related words and terms in the source language with their corresponding translations into the target language. The descriptive contrastive linguistic method has been applied for processing the data selected. The results of the linguistic research reveal that translators mostly employ the translation by equivalence, but sometimes two or more translation techniques complement each other.